The Nurse Workload with Completeness of Nursing Documentation Model Source Oriented Record during Pandemic Period - Tiara Putri Ryandini; Lukman Hakim; Mokhamad Nurhadi; Mei Widyawati; Dyah Pitaloka (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2024)
Ensuring Completeness in nursing documentation is highly important as it reflects a nurse's responsibility and accountability for the tasks performed to meet client needs. However, the heavy workload of Nurses can hinder the implementation of nursing documentation. This study aims to determine the nurse workload and the completeness of nursing documentation with a source-oriented record model during the pandemic (in the Regional General Hospital dr. R. Koesma Tuban) in 2022. This research method uses a correlational analytical research design that examines whether is a relationship between variables with a cross-sectional approach. The population consisted of all nurses in dr. R. Koesma Tuban Hospital, totaling 320 nurses , with a sample size of 155 respondents selected through simple random sampling technique. The Instruments used in this study included a Self-compassion questionnaire consisting of 11 questions and a documentation completeness questionnaire including models source-oriented record consisting of 11 questions. This study utilized the Spearman test with a significance level of = 0.05, the results obtained = 0.02 obtained = 0.02 were less than 0.05, thus accepting the alternative hypothesis (H1). This study concludes that there is a significant correlation between nurse workload and the completeness of nursing documentation with a source-oriented record model during the pandemic in dr. R. Koesma Tuban Hospital in 2022. It is suggested that further research investigate additional causal factors influencing the completeness of the source-oriented record model of nursing documentation.